Improving Small Intestinal Motility in Experimental Acute Necrotising Pancreatitis by Modulating the CPI-17/MLCP Pathway Using Chaiqin Chengqi Decoction. (10th February 2020) - Lin, Ziqi; Zhang, Chenlong; Zhang, Xiaoxin; Shi, Na; Wen, Yongjian; Han, Chengxia; Du, Dan; Liu, Tingting; Jin, Tao; Deng, Lihui; Jiang, Kun; Yang, Xiaonan; et al.
Abstract : Protein kinase C-potentiated inhibitor protein of 17 kDa (CPI-17), a specific inhibitor of myosin light-chain phosphatase (MLCP) regulated by proinflammatory cytokines, is central for calcium sensitisation. We investigated the effects of chaiqin chengqi decoction (CQCQD) on the CPI-17/MLCP pathway in the small intestinal smooth muscle cells (SMCs) and strips (SMS) in an AP model. Necrotising AP was induced in rats by intraperitoneal injections (IPI) of L-ornithine (3.0 g/kg, pH 7.0; hourly × 2) at 1 hour apart; controls received saline. In treatment groups, carbachol (CCh; 60 μ g/kg, IPI) or CQCQD (20 g/kg; 2-hourly × 3, intragastric) was administered. The necrotising AP model was associated with systemic inflammation (serum IL-1 β and TNF- α ) and worsened jejunum histopathology and motility (serum vasoactive intestinal peptide and intestinal fatty acid-binding protein) as the disease progressed. There was decreased intracellular calcium concentration ([Ca 2+ ]i ) SMCs. Contractile function of isolated SMCs was reduced and associated with down-regulated expression of key mRNAs and proteins of the CPI-17/MLCP pathway as well as increased IL-1 β and TNF- α . CQCQD and CCh significantly reversed these changes and the disease severity. These data suggest that CQCQD can improve intestinal motility by modulating the CPI-17/MLCP pathway in small intestinal smooth muscle during AP.